Dig in trigo

Geometry Level 3

If tan ( x + y ) = 8 \tan (x + y) = \sqrt 8 and tan ( x y ) = 2 \tan ( x - y) = \sqrt 2 , then what is tan ( 2 x ) tan ( 2 y ) ? \tan(2x) \tan(2y) ?


The answer is -0.4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Marco Brezzi
Aug 11, 2017

Consider the following identity

tan ( α ± β ) = tan α ± tan β 1 tan α tan β \tan(\alpha\pm\beta)=\dfrac{\tan\alpha\pm\tan\beta}{1\mp\tan\alpha\tan\beta}

So we have

tan ( 2 x ) = tan [ ( x + y ) + ( x y ) ] = tan ( x + y ) + tan ( x y ) 1 tan ( x + y ) tan ( x y ) = 2 2 + 2 1 2 2 2 = 3 2 3 = 2 \begin{aligned} \tan(2x)&=\tan[(x+y)+(x-y)]\\ &=\dfrac{\mathbin{\color{#D61F06}\tan(x+y)}+\mathbin{\color{#3D99F6}\tan(x-y)}}{1-\mathbin{\color{#D61F06}\tan(x+y)}\mathbin{\color{#3D99F6}\tan(x-y)}}\\ &=\dfrac{\mathbin{\color{#D61F06} 2\sqrt{2}}+\mathbin{\color{#3D99F6} \sqrt{2}}}{1-\mathbin{\color{#D61F06} 2\sqrt{2}}\cdot\mathbin{\color{#3D99F6} \sqrt{2}}}=-\dfrac{3\sqrt{2}}{3}=-\sqrt{2} \end{aligned}

tan ( 2 y ) = tan [ ( x + y ) ( x y ) ] = tan ( x + y ) tan ( x y ) 1 + tan ( x + y ) tan ( x y ) = 2 2 2 1 + 2 2 2 = 2 5 \begin{aligned} \tan(2y)&=\tan[(x+y)-(x-y)]\\ &=\dfrac{\mathbin{\color{#D61F06}\tan(x+y)}-\mathbin{\color{#3D99F6}\tan(x-y)}}{1+\mathbin{\color{#D61F06}\tan(x+y)}\mathbin{\color{#3D99F6}\tan(x-y)}}\\ &=\dfrac{\mathbin{\color{#D61F06} 2\sqrt{2}}-\mathbin{\color{#3D99F6} \sqrt{2}}}{1+\mathbin{\color{#D61F06} 2\sqrt{2}}\cdot\mathbin{\color{#3D99F6} \sqrt{2}}}=\dfrac{\sqrt{2}}{5} \end{aligned}

Our answer is 2 × 2 5 = 2 5 = 0.4 -\sqrt{2} \times \dfrac{\sqrt{2}}{5} = - \dfrac25 = \boxed{-0.4} .

Chew-Seong Cheong
Aug 10, 2017

{ tan ( x + y ) = 8 sin ( x + y ) = 8 3 , cos ( x + y ) = 1 3 tan ( x y ) = 2 sin ( x y ) = 2 3 , cos ( x y ) = 1 3 \begin{cases} \tan (x+y) = \sqrt 8 & \implies \sin (x+y) = \frac {\sqrt 8}3, & \cos (x+y) = \frac 13 \\ \tan (x-y) = \sqrt 2 & \implies \sin (x-y) = \sqrt {\frac 23}, & \cos (x-y) = \frac 1{\sqrt 3} \end{cases}

sin ( x + y ) sin ( x y ) = 8 3 2 3 Since sin A sin B = 1 2 ( cos ( A B ) cos ( A + B ) ) 1 2 ( cos 2 y cos 2 x ) = 4 3 3 cos 2 y cos 2 x = 8 3 3 . . . ( 1 ) cos ( x + y ) cos ( x y ) = 1 3 1 3 Since cos A cos B = 1 2 ( cos ( A B ) + cos ( A + B ) ) 1 2 ( cos 2 y + cos 2 x ) = 1 3 3 cos 2 y + cos 2 x = 2 3 3 . . . ( 2 ) \begin{aligned} \sin(x+y) \sin(x-y) & = \frac {\sqrt 8}3 \cdot \sqrt {\frac 23} & \small \color{#3D99F6} \text{Since }\sin A \sin B = \frac 12 (\cos (A-B)-\cos (A+B)) \\ \frac 12 \left(\cos 2y - \cos 2x \right) & = \frac 4{3\sqrt 3} \\ \cos 2y - \cos 2x & = \frac 8{3\sqrt 3} & ...(1) \\ \cos(x+y) \cos(x-y) & = \frac 13 \cdot \frac 1{\sqrt 3} & \small \color{#3D99F6} \text{Since }\cos A \cos B = \frac 12 (\cos (A-B) + \cos (A+B)) \\ \frac 12 \left(\cos 2y + \cos 2x \right) & = \frac 1{3\sqrt 3} \\ \cos 2y + \cos 2x & = \frac 2{3\sqrt 3} & ...(2) \end{aligned}

{ ( 2 ) + ( 1 ) : cos 2 y = 5 27 sin 2 y = 2 27 , tan 2 y = 2 5 ( 2 ) ( 1 ) : cos 2 x = 1 3 sin 2 x = 2 3 , tan 2 x = 2 \begin{cases} (2)+(1): \quad \cos 2y = \frac 5{\sqrt{27}} & \implies \sin 2y = \sqrt {\frac 2{27}}, & \color{#3D99F6} \tan 2y = \frac {\sqrt 2}5 \\ (2)-(1): \quad \cos 2x = - \frac 1{\sqrt 3} & \implies \sin 2x = \sqrt {\frac 23}, & \color{#D61F06} \tan 2x = - \sqrt 2 \end{cases}

Then we have:

tan 2 x tan 2 y = 0.4 \begin{aligned} \ {\color{#D61F06}\tan 2x} \ {\color{#3D99F6} \tan 2y} & = \boxed{-0.4} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...